Scanning tunneling microscopy and spectroscopy of rubrene on clean and graphene-covered metal surfaces - Rothe, Karl; Mehler, Alexander; Néel, Nicolas; Kröger, Jörg (Beilstein Journal of Nanotechnology, 2020)
Rubrene (C42H28) was adsorbed with submonolayer coverage on Pt(111), Au(111), and graphene-covered Pt(111). Adsorption phases and vibronic properties of C42H28 consistently reflect the progressive reduction of the molecule–substrate hybridization. Separate C42H28 clusters are observed on Pt(111) as well as broad molecular resonances. On Au(111) and graphene-covered Pt(111) compact molecular islands with similar unit cells of the superstructure characterize the adsorption phase. The highest occupied molecular orbital of C42H28 on Au(111) exhibits weak vibronic progression while unoccupied molecular resonances appear with a broad line shape. In contrast, vibronic subbands are present for both frontier orbitals of C42H28 on graphene. They are due to different molecular vibrational quanta with distinct Huang–Rhys factors.
Keywords: graphene; metal surfaces; molecular superstructures; rubrene; scanning tunneling microscopy; scanning tunneling spectroscopy; vibronic states